THE METABOLIC ACTIVITY OF THE ADULT RABBIT CHOROID PLEXUS: AN ENZYMATIC HISTOCHEMICAL APPROACH - Al-Dulaymi, Shehab H. Mehenna; Azzawi, Hani T. (Gezira Journal of Health Sciences, 2005)
Objective : To investigate the metabolic activity of the adult rabbit choroid plexus, using succinate dehydrogenase, phosphorylase and α-naphthylacetate esterase as histochemical markers of, the aerobic, glycolytic, and lipolytic pathways,  respectively. Methods : Coverslip-mounted choroid plexus sections of adult rabbits were stained histochemically for the above enzymes. To characterize the esterase isoform(s), sections were incubated with various esterase modifiers before identification of the esterase activity. Sections of liver and kidney (controls) were simultaneously treated as for choroid plexus sections.  Results : Strong reactivity of the choroidal epithelium for both succinate dehydrogenase and esterase was readily detectable, while phosphorylase activity was virtually absent. In contrast to the B-isoform of esterase characteristically dominated the controls, the choroidal esterase activity was attributed mainly to C-isoform .                                                                                                                                                                    Conclusion: The results suggest that the energy required for CSF formation by the adult choroid plexus is derived almost exclusively from aerobic oxidation, including fat metabolism. The high esterase activity in the choroid plexus , and in particular the unique pattern of the choroidal esterase versus the esterase of the controls, were interpreted to offer a potential target for future inhibitors of the energy of fat metabolism and thereby for CSF reduction.